The Improvements in the Prolactin, Thyroid Hormones and Lipid Profiles that are Observed During Three Pregnancy Periods - Khalid .S. Sahab1 , Ali. S. Alsaadi2 , Ammar.M.Kadhim3 (Indian Journal of Forensic Medicine & Toxicology, 2020)
This research was to explore improvements in lipid profile, TSH, T3, T4 and prolactin during threestage of the progress. Pregnancy leads to development in both hormones and biochemistries of thematernal blood. The study involved a control group of 20 non-pregnant women and 30 pregnant and.Automatic hormone analyzer1 and biochemistry automatic analyzer measured hormones, with thelipid profile2. Although T3, T4, TC and TG showed no significant increases in first (p? 0.05) comparedwith the control group, TC and TG increased significantly in the second phase and third stage of pregnancytrimesters and T3 and T4 significantly in the third phase of pregnancy quarter (p ?0.05) compared with thecontrol team (p ?0.05). The results demonstrate a significant increase in prolactin in three stage of pregnancy(p?0.05). No significant increase (p ? 0.05) in comparison with control groups was shown in LDL-C andHDL -C over all phases of the prolactin. Increased prolactin, thyroid hormones and the rise in lipid fractionsfollow normal pregnancy.